2014
DOI: 10.2117/psysoc.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Current and Future Directions of Socio-Ecological Psychology

Abstract: Socio-ecological psychology "investigates how mind and behavior are shaped in part by their natural and social habitats (social ecology), and how natural and social habitats are in turn shaped partly by mind and behavior" (Oishi, 2014, p. 582). Just as the main goal of cultural psychology is to illuminate how individuals and culture make each other up (Shweder, 1991), the main goal of this approach is to illuminate how individuals and social ecologies define each other. Unlike the complex and often abstract co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…The present work dovetails nicely with work demonstrating the importance of the physical context on individuals' success and well-being (Oishi & Graham, 2010;Oishi & Hoffman, 2014;Oishi, Saeki, & Axt, 2015; see also Bonam, Bergsieker, & Eberhardt, 2016). Previous work has shown that physical objects can provide cues as to who belongs in a domain and who does not.…”
Section: Discussionsupporting
confidence: 83%
“…The present work dovetails nicely with work demonstrating the importance of the physical context on individuals' success and well-being (Oishi & Graham, 2010;Oishi & Hoffman, 2014;Oishi, Saeki, & Axt, 2015; see also Bonam, Bergsieker, & Eberhardt, 2016). Previous work has shown that physical objects can provide cues as to who belongs in a domain and who does not.…”
Section: Discussionsupporting
confidence: 83%